Endothelial and Autonomic Dysfunction at Early Stages of Glucose Intolerance and in Metabolic Syndrome - Dimova, Rumyana; Tankova, Tsvetalina; Kirilov, Georgi; Chakarova, Nevena; Grozeva, Greta; Dakovska, Lilia (Hormone and Metabolic Research, 2020)
This study evaluated sE-selectin, Endothelin-1, and cardiovascular autonomic neuropathy (CAN) at early stages of glucose intolerance and in metabolic syndrome (MetS). A total of 87 subjects – 39 males, of mean age 45.7±11.6 years and mean BMI 31.4±6.6 kg/m2, divided according to glucose tolerance and the presence of MetS were enrolled. Glucose tolerance was studied during OGTT. Anthropometric indices, blood pressure, HbA1c, lipids, hsCRP, sE-selectin, Endothelin-1, and immunoreactive insulin were measured. Body composition was assessed by a bioimpedance method (InBody 720, BioSpace). Tissue AGEs accumulation was evaluated by skin autofluorescence (AGE-Reader, DiagnOpticsTM). CAN was assessed by ANX-3.0 technology. In the groups, according to glucose tolerance, the prevalence of CAN was 5.7% in normal glucose tolerance (NGT), 8.6% in prediabetes, and 23.5% in newly diagnosed type 2 diabetes (NDD). In the groups, according to the presence of MetS, the prevalence of CAN was 12.3% in those with MetS and 4.8% in those without MetS. Parasympathetic activity was diminished at rest (p=0.048, 0.015, respectively) in NDD as compared to prediabetes and NGT; and there was a numerically elevated heart rate at rest in NDD in comparison to NGT. There was a negative correlation between parasympathetic tone and waist circumference, BMI, and visceral and total fat. There was no difference in the measured endothelial function markers in the groups according to glucose tolerance and MetS. sE-selectin correlated with HOMA-IR (r=0.275, p=0.048). No association between Endothelin-1 levels and assessed metabolic parameters was observed. There is a high prevalence of CAN at early stages of glucose intolerance and in MetS, due to decreased parasympathetic activity. Slight elevation of glycemia and MetS probably do not affect endothelial function, since sE-selectin seems to be related to insulin resistance.
Keywords: sE-selectin; Endothelin-1; cardiovascular autonomic neuropathy; prediabetes; metabolic syndrome